Influence of calcium on glucose biosensor response and on hydrogen peroxide detection - Labat-Allietta, N.; Thevenot, D.R. (Biosensors & Bioelectronics, 1998)
Of small species capable of reaching a platinum working electrode from biological samples, calcium cations have been found to inhibit significantly glucose biosensor responses. The sensitivities to glucose of sensors immersed in carbonate buffer saline solutions decreased when 0.5 mM calcium chloride was added. The degree of inhibition was proportional to the glucose response in the absence of calcium (0-17% of the normalized current). Likewise, sensor sensitivities to hydrogen peroxide decreased, in the 5-90% range, in the presence of 0.5 mM calcium. Bare Pt-Ir wires show a reversible inhibition of hydrogen peroxide sensitivity. This reversible inhibition is directly related to the decrease of hydrogen peroxide oxidation rate at the platinum anode: this has been evidenced, using rotating disk electrodes, by plotting Koutecky-Levich plots. Such inhibition has been found both for free and chelated calcium cations at levels below 1 mM. Several hypotheses for possible reactions between platinum, hydrogen peroxide and calcium are discussed. (C) 1997 Elsevier Science Limited. All rights reserved.